2007
DOI: 10.1093/nar/gkm1053
|View full text |Cite
|
Sign up to set email alerts
|

The Leu22Pro tumor-associated variant of DNA polymerase beta is dRP lyase deficient

Abstract: Approximately 30% of human tumors characterized to date express DNA polymerase beta (pol β) variant proteins. Two of the polymerase beta cancer-associated variants are sequence-specific mutators, and one of them binds to DNA but has no polymerase activity. The Leu22Pro (L22P) DNA polymerase beta variant was identified in a gastric carcinoma. Leu22 resides within the 8 kDa amino terminal domain of DNA polymerase beta, which exhibits dRP lyase activity. This domain catalyzes the removal of deoxyribose phosphate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 33 publications
(70 reference statements)
1
76
2
Order By: Relevance
“…Leu22Pro tumor-associated variant of polβ is dRP lyase deficient (Dalal et al, 2008). It is being reported that the E295K mutation in polβ which is a gastric cancer-associated variant interferes with base excision repair and induces cellular transformation (Lang et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leu22Pro tumor-associated variant of polβ is dRP lyase deficient (Dalal et al, 2008). It is being reported that the E295K mutation in polβ which is a gastric cancer-associated variant interferes with base excision repair and induces cellular transformation (Lang et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Pol β variants, K289M and I260M have functional phenotypes that could be related to the etiology of human cancer (Lang et al, 2003;Dalal et al, 2005). The Val246 variant was shown to mis-incorporate nucleotides through altered DNA positioning in the active site (Dalal et al, 2008). It was evidenced that expression of the E295K gastric carcinoma-associated pol beta variant (Lang et al, 2007) in mouse cells interferes with BER and induces sister chromatid exchanges and cellular transformation (Lang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Another Leu22Pro tumor-associated variant of polβ is dRP lyase deficient (Dalal et al, 2008). Therefore, any kind of point mutation can change the conformation during the polymerase opening and thereby altering the DNA positioning in the active site (Yang et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The 5′-dRP-containing DNA substrate was prepared just before use, as describe previously (28,29); and the assay was set up according to Prakash et al (30) with minor modifications (SI Text).…”
Section: Methodsmentioning
confidence: 99%